Pre-treatments enhancing biodegradation of EFB fibers for composting - Che Hamzah, Nurul Husna; Yahya, Azmi; Samsu Baharuddin, Azhari; Che Man, Hasfalina (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents a new process to enhance the biodegradation rate of EFB fibers prior to composting which is by performing some new kinds of pre-treatment which are not only economical but also profitable. Rapid composting is the objective of this study and and is achievable by operating high pressure steam pre-treatment combined with acid pre-treatment. Sterilization pre-treatment was operated at 40 psi which is a standard operating procedure for sterilization process in palm oil mills. Acid pre-treatment is a natural biological pre-treatment which utilizing fresh raw POME as a replacement of industrial acid used for enzymatic hydrolysis. Sterilization and acid pre-treatments proved that they are worth to be introduced in local palm oil mills because their chemical reaction resulted a high nutrient compost which has C/N ratio of 5.7 on day 80 of composting whereas a good compost reached maturity state when C/N ratio is below 20. This result proves that its maturity state may have been reached a far ealier which is a success for rapid composting technology. This controlled composting used cylindrical plastic container and regularly monitored to maintain the optimum condition for the microbacteria inside compost.